Improving English Speaking Skill through Intensive Course at SMA YP PGRI 3 Makassar - Fa'adhilah, Wafiyah Asyifah; Jannah, Izzatul; Ainunnisa, Andi Nurul (IJOCSE: Indonesian Journal of Community Services, 2024)
Speaking is a skill that needs to be trained not only in class but also outside class as an extra class. High school students need additional classes to focus on developing speaking skills in English. Moreover, Senior High School students should be equipped with English skills to support their value in order to be able to compete in the world of work on a national and international scale. In addition to sharpening and developing students' English skills, this dedication is also a form of participation to foster the motivation of students to learn English especially in the students of YP PGRI 3 MAKASSAR high school. This method of devotion uses learning and teaching methods. The results of this dedication were able to increase the confidence of the students in speaking, increase knowledge of the importance of English and broaden the students' insight into the English language material as a result of the teaching process. The teaching is done using the student center method where students are more active with interactive learning, i.e. with hands-on practice after the material is taught, this speaking class is also very appreciative with the presence of reflection and reward day at the end of learning. The implications of this dedication are to be a reference for educators who will plunge into the world of education and teaching English especially in improving the English speaking ability of students.